Legal issues of the consent mechanism in the processing of personal data using artificial intelligence - Aziza Donaeva (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article examines the legal significance and practical challenges of consent in the processing of personal data through artificial intelligence technologies. In the digital environment, individuals are not always able to fully understand how their data is collected, analyzed, and used. The complexity of artificial intelligence systems, the opacity of algorithms, and the possibility of using data for secondary purposes raise serious concerns regarding informed, freely given, and conscious consent. The article analyzes these issues from the perspective of national legislation and international approaches and proposes directions for improving the consent mechanism.